2021
DOI: 10.23958/ijirms/vol06-i01/1061
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Ketogenic Diet among Adults with Chronic Disease in Saudi Arabia

Abstract: Introduction: Ketogenic diet was first approached diet in treatment of epilepsy in children, later on, many studies showed its positive effect on adults who have chronic diseases and obesity. The main aim of the diet is to allow the body to reach the state of ketosis by generating energy from fat rather than glucose, and this happen by lowering the carbohydrates, adding moderate protein and high fat, thus letting the body burn fat for fuel. Since more than 50 years studies linked consumption of saturated fat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…[11] Furthermore, another study conducted by Alexandria M. D'Agostino among college students at Midwestern University in the USA found that awareness and understanding of the KD are inconsistent among male college students and are unlikely to affect KD usage due to other factors such as lifestyle habits and values that are more likely to affect KD participation. [12] In Saudi Arabia, studies have been conducted to assess the utilization and efficacy of the KD in adults with chronic diseases [13] and children with epilepsy. [14,15] A recent study was conducted among Saudi students in Jazan that assessed the knowledge and perception of the KD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Furthermore, another study conducted by Alexandria M. D'Agostino among college students at Midwestern University in the USA found that awareness and understanding of the KD are inconsistent among male college students and are unlikely to affect KD usage due to other factors such as lifestyle habits and values that are more likely to affect KD participation. [12] In Saudi Arabia, studies have been conducted to assess the utilization and efficacy of the KD in adults with chronic diseases [13] and children with epilepsy. [14,15] A recent study was conducted among Saudi students in Jazan that assessed the knowledge and perception of the KD.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, studies have been conducted to assess the utilization and efficacy of the KD in adults with chronic diseases [ 13 ] and children with epilepsy. [ 14 , 15 ] A recent study was conducted among Saudi students in Jazan that assessed the knowledge and perception of the KD.…”
Section: Introductionmentioning
confidence: 99%